Randomised controlled trial of home-based walking programmes at and below current recommended levels of exercise in sedentary adults. Issue 9 (14th August 2007) - Tully, Mark A; Cupples, Margaret E; Hart, Nigel D; McEneny, Jane; McGlade, Kieran J; Chan, Wai-Sun; Young, Ian S
Abstract : Objectives: To determine, using unsupervised walking programmes, the effects of exercise at a level lower than currently recommended to improve cardiovascular risk factors and functional capacity. Design: 12 week randomised controlled trial. Setting: Northern Ireland Civil Service; home-based walking. Participants: 106 healthy, sedentary 40 to 61 year old adults of both sexes. Interventions: Participants were randomly allocated to a walking programme (30 minutes brisk walking three days a week (n = 44) or five days a week (n = 42)) or a control group (n = 20). Participants could choose to walk in bouts of at least 10 minutes. They used pedometers to record numbers of steps taken. Intention to treat analysis of changes within groups was done using paired t tests; extent of change (baseline to 12 week measurements) was compared between groups using analysis of variance and Gabriel's post hoc test. Main outcome measures: Blood pressure, serum lipids, body mass index, waist:hip ratio, and functional capacity (using a 10 m shuttle walk test). Main results: 89% (93/106) completed the study. Systolic blood pressure and waist and hip circumferences fell significantly both in the three day group (5 mm Hg, 2.6 cm, and 2.4 cm, respectively) and in the five day group (6 mm Hg, 2.5 cm, and 2.2 cm) (p<0.05). Functional capacity increased in both groups (15%; 11%). Diastolic blood pressure fell in the five day group (3.4 mm Hg, p<0.05). No changes occurred in the control group. Conclusions: This study provides evidence of benefit from exercising at a level below that currently recommended in healthy sedentary adults. Further studies are needed of potential longer term health benefits for a wider community from low levels of exercise.